2012
DOI: 10.2340/16501977-0899
|View full text |Cite
|
Sign up to set email alerts
|

Return to work five years after spinal cord injury inpatient rehabilitation: Is it related to wheelchair capacity at discharge?

Abstract: More than 40% of the participants were able to return to paid work within 5 years after discharge from inpatient rehabilitation. Return to work was related to wheelchair capacity at discharge. It is recommended to train wheelchair capacity during rehabilitation in the context of return to work, since the association with return to work is another benefit of the training of wheelchair capacity in addition to the improvement of mobility and functional independency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Systematic monitoring of wheelchair-specific fitness after inpatient rehabilitation could be part of such a model, since it can support the maintenance of fitness (1). Maintaining wheelchair-specific fitness in people with long-term ScI can help to support health, participation in society and quality of life (3)(4)(5)9). Monitoring can also help to target those in most need of interventions; this need may differ between inactive people with long-term ScI, as indicated by the high variance in fitness in our study.…”
Section: Implications and Limitationsmentioning
confidence: 78%
See 3 more Smart Citations
“…Systematic monitoring of wheelchair-specific fitness after inpatient rehabilitation could be part of such a model, since it can support the maintenance of fitness (1). Maintaining wheelchair-specific fitness in people with long-term ScI can help to support health, participation in society and quality of life (3)(4)(5)9). Monitoring can also help to target those in most need of interventions; this need may differ between inactive people with long-term ScI, as indicated by the high variance in fitness in our study.…”
Section: Implications and Limitationsmentioning
confidence: 78%
“…the mean POpeaks in the subgroups with paraplegia (51 W) and tetraplegia (19 W) were approximately 30% lower than the mean POpeak determined in a systematic review of studies on fitness of people with paraplegia (74 W) and tetraplegia (26 W) (12). Such low POpeak values are alarming, as POpeak has been negatively associated with strain during Adl, health, participation and even quality of life (3)(4)(5)32). Furthermore, mean POpeak in our study (41 W) was approximately equal to that of a group of people at the start of inpatient ScI rehabilitation (35 W) (28).…”
Section: Vo2peak (L/min)mentioning
confidence: 83%
See 2 more Smart Citations
“…That review showed that 20 minutes of moderate to vigorous aerobic exercise, performed twice per week at an intensity of 60%‐65% peak oxygen uptake (normalV˙O 2 ) or 60%‐80% peak heart rate (HR) is required for adults with SCI to gain important fitness benefits. Such fitness benefits have been positively associated with health, participation, and quality of life of adults with SCI [13‐15]. However, normalV˙O 2 and HR measures of exercise intensity cannot be used by many adults with SCI.…”
Section: Introductionmentioning
confidence: 99%